2020
DOI: 10.3390/ijerph17061909
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Examining Effects of Animal Assisted Intervention and Stress Related Symptoms on College Students’ Learning and Study Skills

Abstract: Animal Visitation Programs (AVPs) targeting college students’ stress and academic success have increased, despite limited research on academic outcomes. This randomized controlled trial (N = 349) examined the effects of incorporating levels of Human–animal Interaction (HAI) (0%, 50% or 100%) with therapy dogs in a four-week academic stress management program. Conditions included (1) Academic Stress Management (ASM) content only (0% HAI), (2) Human–animal Interaction only (100% HAI) and (3) equal combinations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…These effects may translate to additional effects on students' academic success, learning, and cognition. For instance, a recent randomized controlled trial ( 51 ) paired a standard academic stress management program with therapy dog interaction; the pairing produced significantly higher levels of self-reported enjoyment, usefulness, self-regulation, and behavior change than the stress management program or dog interaction alone. However, when therapy dog interaction is closely paired with more specific learning experiences, beneficial effects on stress remain, but benefits to academic performance may not manifest.…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
“…These effects may translate to additional effects on students' academic success, learning, and cognition. For instance, a recent randomized controlled trial ( 51 ) paired a standard academic stress management program with therapy dog interaction; the pairing produced significantly higher levels of self-reported enjoyment, usefulness, self-regulation, and behavior change than the stress management program or dog interaction alone. However, when therapy dog interaction is closely paired with more specific learning experiences, beneficial effects on stress remain, but benefits to academic performance may not manifest.…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
“…Although providing this kind of intervention to college and university students is a fairly new undertaking [ 26 ], there is promising evidence that AAIs can, amongst others, result in higher ratings of momentary positive emotions, a reduction in stress-related negative emotions [ 27 , 28 ], psychological and physical markers of stress [ 29 , 30 , 31 , 32 ], anxiety [ 33 , 34 , 35 , 36 ], and homesickness while increasing their satisfaction with life, connectedness to campus [ 37 , 38 ], behavioral aspects of academic success [ 39 ], well-being and improving their social skills as well as their mood [ 29 , 33 , 40 ]. Furthermore, Daltry and Mehr [ 41 ] found that having animals on campus may promote the services offered by student counseling centers on campus, as a lot of students were unaware of them before implementing the AAI.…”
Section: Introductionmentioning
confidence: 99%
“…In general, most studies had more female than male participants, and participants were mostly of “typical” undergraduate age (mean 20.2 years, median 19.7 years). In almost all studies (n=29) the intervention animal was a dog [43,43,44,4670]. Most studies (n=27) used active intervention conditions [43– 45,45,46,50,5255,57,5962,6469,7174], with most taking place in a group setting.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes were grouped into mental health outcomes, physiological outcomes and cognitive outcomes. Mental health outcomes were by far the most common (n=26) [43– 45,48,49,5155,57,59,6268,70,7274], followed by physiological outcomes (n=14) [43,45,47,50,51,54,58,60,62,65,67,70,71,74] and cognitive outcomes (n=9) [44,46,47,53,56,58,61,63,69]. Most reported cognitive outcomes were related to students’ academic performance.…”
Section: Resultsmentioning
confidence: 99%